2015
DOI: 10.1007/s10529-015-1820-6
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity and mechanism of tea polyphenols against Rhizopus stolonifer

Abstract: The mechanism of action might be attributed to direct damage of the mycelium and spore and indirect induction of defensive enzyme activities. TP has the potential to be developed as an alternative to control post-harvest disease of fruit caused by R. stolonifer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…Del mismo modo, las infecciones por hongos han aumentado en los últimos años, debido a la resistencia de los fitopatógenos a los fungicidas, el cual tiene un impacto significativo en la economía debido a las pérdidas postcosecha causadas por varios hongos (Yang & Jiang, 2015). En la última década, hay un gran interés en el estudio de los compuestos naturales como sustitutos de fungicidas sintéticos y un gran número de estudios in vitro ha demostrado que los efectos antifúngicos de los extractos de plantas reducen la incidencia de patógenos postcosecha (Ramos-Guerrero et al, 2018).…”
Section: P a L A B R A S C L A V Eunclassified
See 3 more Smart Citations
“…Del mismo modo, las infecciones por hongos han aumentado en los últimos años, debido a la resistencia de los fitopatógenos a los fungicidas, el cual tiene un impacto significativo en la economía debido a las pérdidas postcosecha causadas por varios hongos (Yang & Jiang, 2015). En la última década, hay un gran interés en el estudio de los compuestos naturales como sustitutos de fungicidas sintéticos y un gran número de estudios in vitro ha demostrado que los efectos antifúngicos de los extractos de plantas reducen la incidencia de patógenos postcosecha (Ramos-Guerrero et al, 2018).…”
Section: P a L A B R A S C L A V Eunclassified
“…In the same way, fungal infections have been increasing in the last years, due to the resistance of phytopathogens to fungicides, which has a significant impact on the economy due to the post-harvest losses caused by various fungi (Yang & Jiang, 2015). In the last decade, there is a great interest in the study of natural compounds as substitutes for synthetic fungicides and a large number of in vitro studies has demonstrated that the antifungal effects of plant extracts reduce the incidence of post-harvest pathogens (Ramos-Guerrero et al, 2018).…”
Section: Materials Vegetalmentioning
confidence: 99%
See 2 more Smart Citations
“…The antifungal experiment was performed using the micro dilution method of Yang and Jiang. 30 Cell suspensions were diluted in sterile SAM to provide initial cell counts of about 10 8 colony-forming units per mL (CFU mL À1 ). Miconazole nitrate (2 mg) was dissolved in DMSO (2 mL) for the subsequent antifungal experiments as the positive control.…”
Section: Antifungal Assaysmentioning
confidence: 99%